2009
DOI: 10.4049/jimmunol.0900612
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expansion of the Monocytic Lineage Directed by Bacterial Infection

Abstract: CCR2-mediated recruitment of Ly6Chigh monocytes is essential for defense against a range of microbial pathogens. Although our understanding of monocyte trafficking to inflammatory sites is increasing, how innate immune inflammation influences monocyte development and maturation during microbial infection remains undefined. Herein, we demonstrate that infection with the intracellular bacterial pathogen Listeria monocytogenes specifically and selectively promotes monopoiesis. Systemic infection with virulent L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 38 publications
8
106
1
Order By: Relevance
“…Recent studies using CCR2 (-/-) mice or highly specific depletion strategies confirmed that monocytes, but not neutrophils, are important mediators in the control infections [9,22]. Furthermore, during certain microbial infection the Gr-1 hi CCR2 + monocytes can differentiate into TipDCs and produce TNF-α, iNOS [11,17,25,26] and favor the clearance of the ongoing infection (Fig. 1) and may promote an adaptive immune response by presenting the antigens to lymphocytes.…”
Section: Infection and Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies using CCR2 (-/-) mice or highly specific depletion strategies confirmed that monocytes, but not neutrophils, are important mediators in the control infections [9,22]. Furthermore, during certain microbial infection the Gr-1 hi CCR2 + monocytes can differentiate into TipDCs and produce TNF-α, iNOS [11,17,25,26] and favor the clearance of the ongoing infection (Fig. 1) and may promote an adaptive immune response by presenting the antigens to lymphocytes.…”
Section: Infection and Injurymentioning
confidence: 99%
“…In humans, the non-classical subset CD14 + CD16 + has been found to play a proinflammatory role. The so-called TipDCs are the direct descendents of the Gr-1 hi CCR2 + monocytes [11,15,17] and favor the clearance of the ongoing infection (Fig. 1).…”
Section: Functionsmentioning
confidence: 99%
“…Although mature monocytes are postmitotic (18), proliferating monocytes have been described in the BM of healthy mice and elsewhere in disease states (28)(29)(30). These immature cells have promonocyte morphology, express the cell surface proteins CD11b and Ly6C, and share functional similarities with mature monocytes.…”
Section: The Bm Is the Major Site Of Monocyte Production In Tumor-beamentioning
confidence: 99%
“…Monocytes are generated from macrophage and DC precursors in the bone marrow and are released in the bloodstream in a CCR2-dependent manner (28)(29)(30). On the basis of chemokine receptor expression and specific surface molecules (31) …”
mentioning
confidence: 99%